Tetramethylpyrazine Analogue T-006 Promotes the Clearance of Alpha-synuclein by Enhancing Proteasome Activity in Parkinson’s Disease Models - Zhou, Hefeng (Neurotherapeutics, 2019)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder worldwide and is characterized in part by the degeneration of dopaminergic neurons in the substantia nigra pars compacta (SNc). The main pathological hallmark of PD is the intraneuronal accumulation of misfolded α-synuclein (α-syn) aggregates. Mutations in the SNCA gene (encoding α-syn) and variations in its copy number are associated with some forms of familial PD. In the present study, T-006, a new tetramethylpyrazine (TMP) derivative with recently reported anti-Alzheimer activity, is shown to significantly promote α-syn degradation in a cellular PD model. Moreover, we illustrate that T-006 inhibits the accumulation of both Triton-soluble and -insoluble forms of α-syn and protects against α-syn-induced neurotoxicity in A53T-α-syn transgenic mice. The mechanism of action of T-006 was verified by evaluation of a potential protein degradation pathway. We found that T-006 promotes α-syn degradation in a proteasome-dependent and autophagy-independent manner. We further confirmed that T-006 enhances proteasome activity by upregulating 20S proteasome subunit β5i (LMP7) protein expression. A functional study revealed that T-006 activates the PKA/Akt/mTOR/p70S6K pathway to trigger LMP7 expression and enhance chymotrypsin-like proteasomal activity. These findings indicate that T-006 is a potent proteasome activator and a potential therapeutic agent for the prevention and treatment of PD and related diseases. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13311-019-00759-8) contains supplementary material, which is available to authorized users.